SEO Risk Dynamics - Carlson, Murray; Fisher, Adlai; Giammarino, Ron (Review of Financial Studies, 2010)
[We theoretically and empirically investigate firm-level risk dynamics around seasoned equity offerings (SEOs). Empirically, beta increases before SEOs and decreases gradually thereafter. Using real options theory, commitment-to-invest generates a gradual postissuance beta decline whereas instantaneous investment and time-to-build do not. In a behavioral theory, systematic mispricing can cause increasing pre-issuance and decreasing post-issuance risk but idiosyncratic mispricing cannot. In the empirical cross-section, investment, own-firm runup, SEO proceeds, and primary issuance—associated with the real options theory—predict beta declines. Sentiment proxies have weaker effects in the full sample, but are significant in a post-1996 subsample. SEOs coincide with low firm-and market-volatility, suggesting volatility-timing in corporate decisions.]